Functional Recovery via Preregenerated Nerve Graft in Rat Sciatic Nerve Injury Model. (1st September 2019) - Khandpur, Umang; Yan, Ying; Ray, Wilson Zachary; MacEwan, Matthew R
Abstract: INTRODUCTION: Patients who have experienced major tissue loss with peripheral nerve injury (eg, limb amputation) may be offered composite tissue allotransplantation (CTA). The return of sensory ability and cosmetic component of CTAs make them an attractive alternative to prosthetic devices. Unfortunately, robust reinnervation especially over great distances remains an issue for hand allotransplants. In this study, we introduce a preregenerated nerve graft to shorten the distance and therefore time to terminal tissue reinnervation, which could improve the utility of CTAs. METHODS: A total of 18 rats weighing 250 to 300 gm each were randomized into 1 of 3 groups: baseline, fresh, or preregenerated. The baseline group underwent sham surgery to obtain baseline functional data. The fresh and preregenerated groups both underwent grafting of the sciatic nerve but the preregenerated group utilized 8-wk preregenerated grafts. At postperative week 8 from distal neurorrhaphy, both groups underwent terminal functional testing via EMG and evoked muscle force. RESULTS: The preregenerated group had significantly greater mean EMG ( P < .05) and maximum tetanic muscle force values ( P < .05) than the fresh group. Mean percent recovery in EMG for the fresh group was 21.95% compared with 81.79% in the preregenerated group. Mean percent recovery in muscle force was 9.46% and 33.15%, respectively. CONCLUSION: The results of this study provide a novel approach to enhance final functional recovery after peripheral nerve injury. The current practice of constructing a nerve stump may be improved by grafting a nerve segment at the time of injury and allowing it to preregenerate into local musculature so that if a CTA is later performed, an expedited and more robust reinnervation could be accomplished.